2017
DOI: 10.22159/ijpps.2017v9i6.18639
|View full text |Cite
|
Sign up to set email alerts
|

LIPID PROFILE PATTERNS AND ASSOCIATION BETWEEN GLYCATED HAEMOGLOBIN (HbA1C) AND ATHEROGENIC INDEX OF PLASMA (AIP) IN DIABETES PATIENTS AT A TERTIARY CARE HOSPITAL IN MALAYSIA

Abstract: Objective: There is lack of data regarding lipid patterns and the relationship of the atherogenic index of plasma (AIP with glycemic control in Malaysian diabetes patients. This study aimed to assess the lipid patterns and association of AIP with HbA1c in diabetes patients at a tertiary care hospital in Malaysia. Methods:The study was conducted on 72 diabetes patients who were randomly chosen and agreed to participate in the study. AIP values were calculated using log triglycerides/high-density lipoprotein (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The findings of this study can provide baseline data for monitoring the effectiveness of national programs for the prevention and control of obesity in Malaysia [21]. Dutta et al found that overweight patients significantly took dominance in a low-risk category and there was no significant correlation between AIP, TC, HDL, LDL, TG, and BMI [22].…”
Section: Resultsmentioning
confidence: 87%
“…The findings of this study can provide baseline data for monitoring the effectiveness of national programs for the prevention and control of obesity in Malaysia [21]. Dutta et al found that overweight patients significantly took dominance in a low-risk category and there was no significant correlation between AIP, TC, HDL, LDL, TG, and BMI [22].…”
Section: Resultsmentioning
confidence: 87%
“…One study reported an increase of one BMI unit caused a 0.009 mm increase in CIMT and an increase of 1 year in age caused a 0.011 mm increase in CIMT in their study [23]. Butt et al [25] reported that overweight patients significantly took dominance in a low-risk category and he did not found a significant correlation between HDL, LDL, TC, TG, and BMI.…”
Section: Mugada and Kolakotamentioning
confidence: 90%
“…According to a study conducted in Malaysia, lipid abnormalities are frequently found in diabetes patients and are associated with increased risk of CHD [18].…”
Section: Discussionmentioning
confidence: 99%